Beyond Equilibria: Mechanisms for Repeated Combinatorial Auctions - Lucier, Brendan (Innovations in Theoretical Computer Science (ITCS) 2010, 2010)
We study the design of mechanisms in combinatorial auction domains. We focus on settings where the auction is repeated, motivated by auctions for licenses or advertising space. We consider models of agent behaviour in which they either apply common learning techniques to minimize the regret of their bidding strategies, or apply short-sighted best-response strategies. We ask: when can a black-box approximation algorithm for the base auction problem be converted into a mechanism that approximately preserves the original algorithm's approximation factor on average over many iterations? We present a general reduction for a broad class of algorithms when agents minimize external regret. We also present a new mechanism for the combinatorial auction problem that attains an O(√m) approximation on average when agents apply best-response dynamics.